Spectrophotometric Studies on Some 1,3,5-Triphenyl Formazans - El-Hawary, W.F. (Asian Journal of Chemistry, 2010)
Some 1,3,5-triphenyl formazans were prepared. The spectra of, these compounds were scanned in different organic solvents and water. The values of wavelength maxima (λmax) of the bands and the corresponding molar absorptivities (εmax) were calculated. The spectra in ethanol display mainly three sets of bands, each comprising four bands lying at wavelength ranges 222-265, 250-303, 337-388 and 417-505 nm respectively. The bands were assigned to the different electronic transitions. The effect of substituents on the position of λmax was studied. The effect of different solvents on the position of the C.T. bands was studied, an attempt to correlate the position of these bands with different solvent parameters was tried. It was found that, there is no single parameter governing the band shift, but the shift in band position is the resultant of the effect of different parameters.